Trapped in My Roles as a Woman With No Help: Experiences of Intimate Partner Violence Against Chinese Women - Cao, Jiepin (Violence against women, 2023)
An understanding of intimate partner violence (IPV) experiences is a crucial first step toward shaping effective responses. However, relevant knowledge among Chinese women is scant. This study described Chinese women’s IPV experiences by analyzing 46 posts shared by 42 women on a public online forum. Five overarching themes were identified using conventional qualitative content analysis: being trapped in my roles, no power in the relationship, the struggles are real but I need to tolerate, I want to leave but have no help, and hope for the future. This study has important implications for future research, practice, and education.